2014
DOI: 10.1124/jpet.114.219493
|View full text |Cite
|
Sign up to set email alerts
|

Polythiol-Containing, Recombinant Mannosylated-Albumin Is a Superior CD68+/CD206+Kupffer Cell–Targeted Nanoantioxidant for Treatment of Two Acute Hepatitis Models

Abstract: Since reactive oxygen species (ROS) derived from Kupffer cells (KC), especially CD681 KC, play a key role in the induction of hepatic oxidative stress and injuries, we developed a polythiolatedand mannosylated human serum albumin (SH-Man-HSA), which functions as a novel nanoantioxidant for delivering thiol to CD68 1 KC. In vitro electron paramagnetic resonance coupled with pharmacokinetics and immunohistochemical studies showed that SH-Man-HSA possessed powerful radical-scavenging activity and rapidly and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…We recently developed a recombinant neoglyco-human serum albumin (Man-HSA) which possesses a bulky sugar chain consisting of approximately 12 mannose residues that are linked to human serum albumin (HSA) using site-directed mutagenesis and an expression system by pichia pastoris. 20) Our pharmacokinetic experiment in mice showed that more than 60% of the Man-HSA migrated to the liver after its intravenous administration. 20) In addition, we verified that Man-HSA functions as a CD68 + Kupffer cell-targeting drug carrier that is mediated by the mannose receptor C type 1 (CD206).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…We recently developed a recombinant neoglyco-human serum albumin (Man-HSA) which possesses a bulky sugar chain consisting of approximately 12 mannose residues that are linked to human serum albumin (HSA) using site-directed mutagenesis and an expression system by pichia pastoris. 20) Our pharmacokinetic experiment in mice showed that more than 60% of the Man-HSA migrated to the liver after its intravenous administration. 20) In addition, we verified that Man-HSA functions as a CD68 + Kupffer cell-targeting drug carrier that is mediated by the mannose receptor C type 1 (CD206).…”
Section: Introductionmentioning
confidence: 90%
“…20) Our pharmacokinetic experiment in mice showed that more than 60% of the Man-HSA migrated to the liver after its intravenous administration. 20) In addition, we verified that Man-HSA functions as a CD68 + Kupffer cell-targeting drug carrier that is mediated by the mannose receptor C type 1 (CD206). 21) More recently, we developed a Kupffer cell-targeting nanoantioxidant, namely polythiolated and mannosylated human serum albumin (SH-Man-HSA), by loading Man-HSA with poly-thiol groups (7.5 mol thiol/mol Man-HSA).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taking advantage of this liver-specific distribution characteristic, we succeeded in using this highly Man-rHSA as a nitric oxide (NO) carrier in the treatment of hepatic ischemia/reperfusion injury [ 10 ]. Interestingly, Man-rHSA was selectively targeted to mannose receptors (CD206 + ) on CD68 + Kupffer cells [ 11 ]. This means that Man-rHSA has great potential for use as a drug carrier for hepatopathy related to reactive oxygen species (ROS) because CD68 + Kupffer cells can produce relatively high levels of ROS, which play a major role in the progression of liver pathologic conditions [ 12 ].…”
Section: Albumin-based Productsmentioning
confidence: 99%
“…This means that Man-rHSA has great potential for use as a drug carrier for hepatopathy related to reactive oxygen species (ROS) because CD68 + Kupffer cells can produce relatively high levels of ROS, which play a major role in the progression of liver pathologic conditions [ 12 ]. In fact, polythiolated- and mannosylated-rHSA (SH-Man-rHSA) showed excellent hepatoprotective action against both concanavalin A-induced and acetaminophen-induced hepatitis [ 11 ].…”
Section: Albumin-based Productsmentioning
confidence: 99%